(untitled) (Journal on studies and research of academic knowledge, 2021)
Parasitic diseases have a negative economic impact because they affect the reproduction and performance of species submitted to exploitation. Gastrointestinal parasites generate multiple digestive and metabolic disorders in animals, which results in low productivity, mainly a lower weight gain in the overwintering veals. There are different types of pasturage systems. Nonetheless, in this work the rotational Voisin and continuous pasturage systems were studied. In this research work the prevalence of gastrointestinal parasites in these two pasture systems were compared. The population studied were part of two groups: cattle in rearing state in the Voisin system and adult cattle for the continuous system. For the analysis of the samples the qualitative methods of simple and quantitative flotation were used, by recounting in Mac camera. Master from samples of fresh feces, said determinations were carried out in 120 days, and every 30 days extractions and laboratorial determinations were made for each system of pasturage.